Pengaruh Gender, Religiusitas dan Sikap Love of Money Terhadap Etika Penggelapan Pajak UMKM di Malang Raya - Kamaliah, Roudhoh Salsabila; Afifudin, Afifudin; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Gender, religiosity and love of money are factors that allow a person to act unethically in carrying out his tax obligations. This study aims to determine the effect of gender, religiosity and love of money attitudes on the tax evasion ethics of MSMEs in Malang. This research is a quantitative research using primary data. The sampling technique in this study was carried out by purposive sampling. The results of this study indicate: 1) Gender, religiosity and love of money attitudes have a significant effect on the MSME tax evasion ethics simultaneously, 2) The results of the hypothesis test show that gender has a significant positive effect on tax evasion ethics, 3) The results of the hypothesis test show that religiosity has an effect significant positive effect on the ethics of tax evasion, 4) The results of the hypothesis test show that the attitude of love of money has a significant positive effect on the ethics of tax evasion.Keywords: Gender, Religious, Love of Money, Tax Evasion